Women survivors of intimate partner violence talk about using e-health during pregnancy: a focus group study - Rodrigo Fernández López; Sabina de-; Stella Martin-; Juan Carlos Torres Cantero; Jesús L. Megías; Antonella Ludmila Zapata-Calvente (BMC, 2022)
Abstract Background Pregnancy is a period of particular vulnerability to experience intimate partner violence against women (IPVAW). eHealth strategies have been implemented to identify women exposed to IPVAW and to combat the abuse and empower them, but there is a lack of evidence on the use of these strategies among pregnant women. This work aims to identify the needs, concerns and preferences of survivors about the use of eHealth strategies to counsel and empower pregnant victims of IPVAW in antenatal care. Methods A focus group of six IPVAW survivors who had been pregnant was conducted and open questions about the use of eHealth strategies were asked. The session was recorded, transcribed and thematically analyzed. We identified three main themes: needs and worries of pregnant women experiencing IPVAW, key aspects of video counseling sessions and usefulness of safety planning apps. Results Women highlighted the relevant role of healthcare professionals-especially midwives-in the identification of IPVAW and the wellbeing of their children as one of the main concerns. They perceived video counseling and safety planning apps as valuable resources. The preferred contents for a video counseling intervention were awareness-raising of the situation, self-esteem and legal advice. They also proposed safety and pregnant-related aspects that should be taken into account in the design of the video counseling sessions and the safety planning app. Conclusions Video counseling sessions and safety planning apps are potentially useful tools to counsel and empower women who experience IPVAW during pregnancy. Midwives play a key role in this endeavor.